'Behind closed doors, no one sees, no one knows': hepatitis C, stigma and treatment-as-prevention in prison. Issue 2 (14th March 2020) - Rance, Jake; Lafferty, Lise; Treloar, Carla
ABSTRACT: The recent advent of new, highly effective, direct-acting antivirals (DAAs) is dramatically reshaping the hepatitis C virus (HCV) treatment landscape and prisons are set to play an important role. While there is a substantial literature addressing the centrality of stigma to experiences of living with HCV in the community, including as a barrier to treatment, scant attention has been paid to documenting how HCV-stigma figures within the distinct sociality of prison life. This article focuses on initial, pretreatment interviews with prisoner participants ( n = 32) from the first, real-world trial of HCV 'treatment-as-prevention' in prison: Australia's Surveillance and Treatment of Prisoners with Hepatitis C (SToP-C) study. Drawing on recent developments in stigma theory alongside Goffman's original insights, we posit HCV-stigma as a relational, contingent and political process, materialised across the network of power relations in prison. Participant accounts describe a complex picture, with reports ranging from those suggesting the 'normalisation' of HCV to those detailing the potential effects of HCV-stigma, including additional disciplinary attention from officers and/or the rejection from peer networks by fellow prisoners. While acknowledging the limiting effects HCV-stigma may yet have on treatment-as-prevention efforts, we speculate that with committed political leadership, operational investment, sufficient prisoner engagement, interventions such as SToP-C may also afford opportunities for such effects to be challenged, disrupted, and even left behind.